Normative motherhood : regulations, representations, and reclamations - O'Reilly, Andrea, 1961- (Demeter Press, 2023)
"A central aim of motherhood studies is to examine and theorize normative motherhood. Where does it come from? What are its defining features and demands? How does it work as a regulatory discourse and practice across differences of age, class, race, ability, sexuality, and region? What is the impact of normative motherhood on women's lives? What does an intersectional analysis of normative motherhood reveal? How is normative motherhood reflected and enacted in public policy, workplace practices, family arrangements and so on? How is normative motherhood represented and resisted in literature, art, photography, and film? How do or may women resist normative motherhood? This collection explores these questions of normative motherhood under three interrelated topics: Regulations, Representations, and Reclamations."--